2018
DOI: 10.1002/jctb.5668
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced plant growth promoting role of mPEG‐PLGA‐based nanoparticles as an activator protein PeaT1 carrier in wheat (Triticum aestivum L.)

Abstract: BACKGROUND Developing new types of bioproducts using innovative nanotechnology is one of the potentially effective options for enhancing agricultural production and reducing environmental agrochemical pollution. As a bioagent derived from fungi, activator protein can promote growth and control diseases by activating the plant immune system. Meanwhile, the nanocarrier can protect the protein within and prolong its efficiency through controlled release. RESULTS In our study, a new kind of plant nano‐activator wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 36 publications
0
3
0
1
Order By: Relevance
“…The protein-loaded mPEG-PLGA NPs increased the photosynthetic parameters such as Chl content in wheat (Gao et al 2018). CdO NPs decreased CO2 absorption and also inhibited energy transportation from PSII to Calvin cycle in barley (Večeřová et al 2016).…”
Section: Other Metal Nanoparticlesmentioning
confidence: 98%
“…The protein-loaded mPEG-PLGA NPs increased the photosynthetic parameters such as Chl content in wheat (Gao et al 2018). CdO NPs decreased CO2 absorption and also inhibited energy transportation from PSII to Calvin cycle in barley (Večeřová et al 2016).…”
Section: Other Metal Nanoparticlesmentioning
confidence: 98%
“…Nanopartiküllerin bitkisel sistemlerde abiyotik stres faktörlerine karşı uygulanmaları Nanopartiküller; genellikle tohum çimlenmesini iyileştirmek, bitki büyümesini ve verimini artırmak, bitki genetik modifikasyonunu sağlamak, biyoaktif bileşiklerin üretimini iyileştirmek ve bitki korumasını sağlamak için yaygın olarak kullanılmaktadır [11 12]. Bitkilerde nanopartikül uygulamaları, çoğunlukla biyotik ve abiyotik strese karşı bitkilerdeki dayanıklılığı artırmaya ve dayanıklılık ile ilişkili yolakları harekete geçirmeye yöneliktir [13,14,15]. Bitkiler durağan oldukları için tuzluluk, kuraklık, yüksek ve düşük sıcaklıklar, ağır metaller, taşkın, yüksek ve düşük ışık yoğunlukları, ultraviyole (UV) vb.…”
Section: Nanopartiküllerin öZellikleri Ve Bitki Sistemlerinde Genel K...unclassified
“…production. Similarly, Gao et al (2018) developed a novel method of plant activator by encapsulating an activator (protein PeaT1) in polymeric NPs, and the results showed that nanoactivators significantly improved wheat growth. In addition, given the natural composition of polymer-based NPs, overcoming regulatory hurdles and getting public acceptance is likely to be less difficult.…”
Section: Polymeric Npsmentioning
confidence: 99%